ANALISIS PROMOSI DAN AFFILIASI MARKETING TERHADAP OKUPANSI HOTEL NON JARINGAN DI KOTA BATAM - Desrini Ningsih; Putu Hari Kurniawan (Universitas Putera Batam, 2019)
The purpose of this research is to analyse promotion and Affiliate marketing in boosting room sales in non-networked hotel guests. In carrying out operations the hotel can use social media to conduct promotional activities. By doing this marketing strategy the hotel will get a better spotlight from users because based on the number of online travel users with the help of social media is the highest in Southeast Asia to the present. Of course in its implementation using direct channel as a business role model, the role of online travel agency to make room booking with price promotion with profit margin favorable for both parties. In the implementation of online travel agents have a risk when not able to sell the package on the prospective visitors of the hotel. We use quantitative explanatory research models using accidental sampling at 60 non-network hotels in Batam is used as a respondent scattered in Batam city. The results obtained from two supporting variables namely promotion and affiliate Marketing showed positive results. The test results showed that non-network hotel promotion and business affiliations from online travel agencies played an important role in the hotel room sales assessment process.